The Indus Valley and Early Iran. With a Forward by Sir Mortimer Wheeler - Khan, F. A. (1964)
I. The Geographical Setting: Indus Valley and Iran; Physical Features of Iran; The Borderlands of Iran; Ancient Routes between the Indus Valley and Iran. II. Cultural Relationship; Indus Valley and Baluchistan; Common Pottery Motifs and Designs of Harappa Culture and Iran; Relationship between Harappa Culture and South-West Iran; Relation between Harappa Culture and North-East Iran. III. Further Excavations in the Indus Valley: Kot Diji and Amri; Kot Diji Culture; Harappa Culture Pottery; Kot Diji Culture Pottery; Amri Culture; Amri Culture Pottery. Appendices: Chronological Table; Geographical Tables; Select Bibliography; Bibliographical References to Illustrations; Rs. 15.00.